In Silico Study of Secondary Metabolite in Vanilla planifolia to inhibit NUDT5 as Breast Cancer Target - Alim El-Hakim; Anggiresti Kinasih; Rachmi Putri; Saifa Usni Putri; Febri Yuda Kurniawan; Endang Semiarti (Nusantara Science and Technology Proceedings)
Breast cancer is a non-communicable disease that is the main killer for most women in the world. One of ten women with breast cancer will not survive more than five years after diagnosis. Breast cancer cases in Indonesia have been increased annually. As a nucleotide-metabolizing enzyme, NUDT5 (NUDIX hydrolase) catalyzes ADP to ATP nuclear that is used for cell proliferation. NUDT5 is a regulator of tumor driver in breast cancer proliferation. ATP nuclear synthesis can be blocked by inhibiting the NUDT5. The study of potential therapeutic inhibitors for NUDT5 was increased because the current treatment for breast cancer has side effects. Vanilla planifolia is a commercial plant from Orchidaceae which contains secondary metabolites and medicinal potential. This research aims to examine the metabolite of V. planifolia as the inhibitor of NUDT5 activity using molecular docking studies. V. planifolia metabolite and NUDT5 (5nwh) 3D structure were downloaded from the database (RSCB, Pubchem, and Dr. Duke), then the prediction of ADME (absorption, distribution, metabolism, and excretion) and potential bioactivity of the metabolite was analyzed by online structure-based prediction (SwissADME and Way2drug). After that, molecular docking was performed by AutoDock Vina. Three metabolites with the highest binding affinity scores were analyzed by visualization software (Discovery Studio). The result shows that Naphthalene, Caproic acid, Trimethylacetophenone, and Methyleicosane have the highest binding affinity. This result indicated that Naphthalene, Caproic acid, Trimethylacetophenone have the potential effect to inhibit NUDT5 enzyme thus decrease the potential of breast cancer.